Gibbon ape leukemia virus and the amphotropic murine leukemia virus 4070A exhibit an unusual interference pattern on E36 Chinese hamster cells. - Eglitis, M A (1993)
The gibbon ape leukemia virus (GaLV), the amphotropic mouse leukemia virus (A-MLV) 4070A, and the xenotropic mouse leukemia virus (X-MLV) exhibit wide but not identical species host ranges. However, most Chinese hamster cells resist infection by all three viruses. We have now determined that the Chinese hamster cell line E36 differs from other Chinese hamster cell lines in that it is susceptible to infection by wild-type GaLV, A-MLV, and X-MLV. Surprisingly, analysis of the interference pattern of GaLV and A-MLV in E36 cells indicated that GaLV and A-MLV interfere in a nonreciprocal fashion. E36 cells productively infected with GaLV were resistant to superinfection by both GaLV and amphotropically packaged recombinant retroviral vectors. In contrast, E36 cells infected with A-MLV were resistant to superinfection with an amphotropic vector but could still be infected by a GaLV vector. These results imply the existence of a receptor on E36 cells that interacts with both GaLV and A-MLV.